Gender Parity in Adoptability of Google Classroom among Rural College Students with Special Reference to Selected Rural Villages - Vinuchakravarthi, V.; Vikraman, A.; Srinivasan, S. (Indian Journal of Computer Science, 2022)
This study is aimed at analysing whether there is an influence of gender in effective utilization of Google Classroom among college students in rural areas. Sample size of the study was 204 and was selected by Simple Random method. ANOVA was used to analyze the data. The result of the study indicates that there is no impact of gender in the effective utilization of Google Classroom and both the genders are comfortable using Google Classroom. The result further indicates that teachers play a significant role in educating students about Google classroom and mobile is the preferred mode for studying online across all genders.